Run for your life a novel - Patterson, James 1947-; Ledwidge, Michael (New York Little, Brown and Co., 2009)
A calculating killer who calls himself The Teacher is taking on New York City, killing the powerful and the arrogant. Discovering a secret pattern to The Teacher's lessons, Detective Mike Bennett realizes he has just hours to save New York from the greatest disaster in history.
Keywords: Rich people -- Fiction; Serial murderers -- Fiction; New York (N.Y.) -- Fiction; Mystery fiction; Suspense fiction